(untitled) (International journal of artificial intelligence, 2024)
This article reveals the features of innovative management of the education system from a scientific and practical point of view. It also reveals the role and significance of state policy in increasing the innovativeness of the higher education system, the effective use of innovative educational technologies and innovative management technologies of foreign countries, the development and promotion of social and technological innovations. The article deals with the concept of innovation, the problems of managing the innovation process in the field of education according to the methodology of functional modeling. The managerial aspect of supporting the creation and implementation of innovations in educational organizations is analyzed in detail from a scientific and practical point of view.